Use, Perceptions and Attitudes of Cognitive and Sports Performance Enhancing Substances Among University Students - Constantinou, Demitri; Aguiyi, Ivan (Frontiers in Sports and Active Living, 2022)
Introduction: The use of prohibited performance-enhancing substances (PES) is well documented amongst athletes, and the academic environment is not spared. In addition to their use to enhance sporting performance, they may be used for cognitive and academic achievement, specifically through the use of neuroactive substances. The latter in particular is under-researched and poses public health risks. Understanding the extent and reasons for using or not using PES by university students will assist in addressing further research, and means to deter their use. Aim of the study: This study aimed to explore the prevalence, attitude, and perceptions of the use of both sport and academic performance-enhancing substances by students at two universities in Johannesburg, South Africa. Methods: The study utilized a cross-sectional, descriptive survey design using a self-administered online questionnaire. All registered students were invited to participate via email using the university communications modes, with a link to a Google Forms questionnaire. Data were collected anonymously and ethical approval was granted for the study. Results: The sample size of responses with completed data was 548, comprising predominantly female and undergraduate students, with 32 (6%) indicating current or past use of PES. Amongst the prohibited substances used, neuroactive drugs were mostly used, with marijuana the highest followed by stimulants. The most popular reasons were for academic and cognitive performance. Most responded with what would be deemed ethically appropriate answers on the perception of PES use and 72% of the participants believe that a drug-testing program will prevent their use of in the university, and further, that educational programs will help improve students’ knowledge of PES. Conclusion: Although relatively low, university students use performance- enhancing substances, mostly for cognitive enhancement using neuroactive stimulants. Most believe that the use of all forms of PES is high amongst their peers; and favour education and testing programs, suggesting that intervention programs may be effective. Better defined research should be conducted to unpack the broad findings in this study.